Thanksgiving Day - Balfour, Barbara (New York Weigl Publishers, 2007)
Thanksgiving Day is a national holiday held on the fourth Thursday of November. It was first celebrated more than 370 years ago. Thanksgiving became an official national holiday in the United States in 1863.
Elementary
Keywords: Thanksgiving Day